2020
DOI: 10.21203/rs.3.rs-104496/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of Life of University Students During The COVID-19 Pandemic: Age, History of Medical Illness, Religious Coping, COVID-19 Related Stressors, Psychological Factors and Social Support Were Predictive of Quality of Life

Abstract: Background: In Malaysia, the coronavirus disease 2019 (COVID-19) began to spread in March 2020, and the infection has not been fully controlled since then. Despite the significant impact of COVID-19 on mental health among university students, data on the related quality of life (QoL) are lacking in this group of the population. This study aimed to evaluate QoL and determine its association with various factors and social support in a cohort of Malaysian university students during the COVID-19 pandemic. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…According to past researchers, one's quality of life tends to elevate or improve when social support is received, and those who live alone are perceived to experience a higher level of anxiety and depression (Bolatov et al, 2021;Elmer, Mepham, & Stadtfeld, 2020;Wei, 2020). In other words, it is important to have a supportive network such as friends and the university (Sundarasen et al, 2020;Stempel, Alemi, Morgan, & Ingram, 2020) and from family (Abdullah, Murad, Teoh, & Mohamad, 2020). This research provides insight to the university management on the importance of students' mental status, as the neglect of it ruins the quality of students' life and their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…According to past researchers, one's quality of life tends to elevate or improve when social support is received, and those who live alone are perceived to experience a higher level of anxiety and depression (Bolatov et al, 2021;Elmer, Mepham, & Stadtfeld, 2020;Wei, 2020). In other words, it is important to have a supportive network such as friends and the university (Sundarasen et al, 2020;Stempel, Alemi, Morgan, & Ingram, 2020) and from family (Abdullah, Murad, Teoh, & Mohamad, 2020). This research provides insight to the university management on the importance of students' mental status, as the neglect of it ruins the quality of students' life and their academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted in the United States among lower-income undergraduate students revealed negative online learning experiences due to a sudden transition (Aucejo, French, Araya, & Zafar, 2020). While another study conducted by Abdullah et al (2020) disclosed that even when the MCO ended in May 2020, university students in Malaysia tended to exhibit lower psychological and social relationships. Another study conducted in India and Spain also revealed the negative impact of COVID-19 on individual emotions as the respondents develop feelings of loneliness, sadness, anxiety, and frustration (Grover, Sahoo, Mehra, Avasthi, Tripathi, Subrahmanyan, & Chakraborty, 2020: Odriozola-González, Planchuelo-Gómez, Irurtia & de Luis-García, (2020.…”
Section: Introductionmentioning
confidence: 89%
“…With no alternative solution to escape from the COVID pandemic, the government took prompt action to implement the Movement Control Order (MCO) to curb the outbreak from 18 March to 12 May 2020 (MDBC, 2020). All social, religious, sporting, and cultural gatherings were banned except for essential services (Abdullah, Murad, Teoh, & Mohamad, 2020). During the MCO, people were confined for a certain period of social isolation (Sundarasen, Chinna, Kamaludin, Nurunnabi, Baloch, Khoshaim& Sukayt, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor-faktor ini diduga dapat memicu stres dan pada akhirnya dapat mempengaruhi kualitas hidup mahasiswa kedokteran (Malibary et al, 2019). Terlebih lagi di masa pandemi COVID-19, mahasiswa mengalami perubahan pola kehidupan maupun sistem pembelajaran, yang mana perubahan tersebut dapat berpengaruh terhadap kualitas hidupnya (Abdullah et al, 2020). Di Indonesia, publikasi penelitian mengenai gambaran kualitas hidup pada mahasiswa di Fakultas Kedokteran masih sangat terbatas.…”
Section: Pendahuluanunclassified